Nano-MoO2 activates peroxymonosulfate for the degradation of PAH derivatives. (15th March 2021) - Chen, Xuwen; Vione, Davide; Borch, Thomas; Wang, Jian; Gao, Yanzheng
Highlights: The first study of PAH derivatives removal in nano-MoO2 /peroxymonosulfate system. Nano-MoO2 is a novel activator with high catalytic activity on peroxymonosulfate. Nano-MoO2 activation of peroxymonosulfate produces SO4 −, OH, O2 − and 1 O2 . Mo(IV) can be regenerated from the reduction of Mo(VI) on the nano-MoO2 surface. It is a negative correlation between electrostatic potential and degradation rate. Abstract: The rapid and efficient degradation of polycyclic aromatic hydrocarbon (PAH) derivatives with toxicological properties remains a substantial challenge. In this study, a cost-effective and eco-friendly catalyst, nano-MoO2 (0.05 g L −1 ), exhibited excellent performance in activating 4.0 mmol L −1 peroxymonosulfate (PMS) for the degradation of naphthalene derivatives with 1 mg L −1 in aqueous systems; these derivatives include 1-methylnaphthalene, 1-nitronaphthalene, 1-chloronaphthalene, 1-naphthylamine and 1-naphthol, with high degradation rates of 87.52%, 86.23%, 97.87%, 99.74%, and 77.16%. Nano-MoO2 acts as an electron donor by transferring an electron causing O-O bond of PMS to cleave producing SO4 · −, and later · OH. Electron paramagnetic resonance (EPR) analysis combined with free radical quenching research indicated that SO4 · − and · OH dominated the degradation of naphthalene derivatives, and O2 · − and 1 O2 participated in the processes. X-ray photoelectron spectroscopy (XPS) revealed the transformation of Mo(IV) to Mo(V) and Mo(VI), which suggested that the activation process proceeded via electron transfer from nano-MoO2 to PMS. The applicability of the nano-MoO2 /PMS system in influencing parameters and stability was explored. The degradation pathways were primarily elucidated for each naphthalene derivative based on the intermediates identified in the systems. The -CH3, -NO2, -Cl, -OH substituents increased the positive electrostatic potential (ESP) on the molecular surface of 1-methylnaphthalene, 1-nitronaphthalene, 1-chloronaphthalene, and 1-naphthol, which reduced the electrophilic reaction and electron transfer between the reactive species and pollutants, leading to a lower degradation rate of naphthalene derivatives than the parent compound. However, the effect of -NH2 substituents is the opposite. These findings suggest that nano-MoO2 may aid as a novel catalyst in the future remediation of environments polluted with PAH derivatives. Graphical Abstract: Image, graphical abstract